Environment & Health (new in 2023) - Environment & Health (new in 2023) (American Chemical Society, 2026)
Environment & Health, a peer-reviewed, open access journal, is committed to exploring the relationship between the environment and human health. As a premier journal for multidisciplinary research, Environment & Health reports the health consequences for individuals and communities of changing and hazardous environmental factors. In supporting the UN Sustainable Development Goals, the journal aims to help formulate policies to create a healthier world. Topics of interest include, but are not limited to: Air, water, and soil pollution; Exposomics; Environmental epidemiology; Innovative analytical methodology and instrumentation; Environmental toxicology; Environmental microbiology, pathogen, and environmental transmission mechanisms of diseases; Environmental modeling, bioinformatics, and artificial intelligence; Emerging contaminants; Climate change and related health effects; Health impacts of energy evolution and carbon neutralization; Food and drinking water safety; Occupational exposure and medicine; Innovations in environmental technologies for better health; Policies and international relations concerned with environmental health.
FI 6.3
Q1
Keywords: Earth; Space & Environmental Sciences; Ecotoxicology & Pollution Science; Ciencias de la contaminación; Ecotoxicología; Acuerdos transformativos; Transformative agreements; Exposición ambiental; Calidad ambiental; Riesgos para la salud